Cell-Free Approach for Non-canonical Amino Acids Incorporation Into Polypeptides - Cui, Zhenling; Johnston, Wayne A.; Alexandrov, Kirill (Frontiers in Bioengineering and Biotechnology, 2020)
Synthetic biology holds promise to revolutionize the life sciences and biomedicine via expansion of macromolecular diversity outside the natural chemical space. Use of noncanonical amino acids (ncAAs) via codon reassignment has found diverse applications in protein structure and interaction analysis, introduction of post-translational modifications, production of constrained peptides, antibody-drug conjugates, and novel enzymes. However, simultaneously encoding multiple ncAAs in vivo requires complex engineering and is sometimes restricted by the cell’s poor uptake of ncAAs. In contrast the open nature of cell-free protein synthesis systems offers much greater freedom for manipulation and repurposing of the biosynthetic machinery by controlling the level and identity of translational components and reagents, and allows simultaneous incorporation of multiple ncAAs with non-canonical side chains and even backbones (N-methyl, D-, β-amino acids, α-hydroxy acids etc.). This review focuses on the two most used Escherichia coli-based cell-free protein synthesis systems; cell extract- and PURE-based systems. The former is a biological mixture with >500 proteins, while the latter consists of 38 individually purified biomolecules. We delineate compositions of these two systems and discuss their respective advantages and applications. Also, we dissect the translational components required for ncAA incorporation and compile lists of genetically encoded ncAAs via different acylation approaches. We highlight the recent progress using unnatural nucleobase pairs to increase the repertoire of orthogonal codons, as well as using tRNA-specific ribozymes for in situ acylation. We summarize advances in engineering of translational machinery such as tRNAs, aminoacyl-tRNA synthetases, elongation factors and ribosomes to achieve efficient incorporation of structurally challenging ncAAs. We note that, many engineered components of biosynthetic machinery are developed for the use in vivo but are equally applicable to the in vitro systems. These are included in the review to provide a comprehensive overview for ncAA incorporation and offer new insights for the future development in cell-free systems. Finally, we highlight the exciting progress in the genomic engineering, resulting in E. coli strains free of amber codons and some redundant sense codons. These strains can be used for preparation of cell extracts offering multiple reassignment options.